Soil organic carbon in a toposequence in the semiarid of Paraíba, Brazil (Research, Society and Development, 2020)
Organic carbon is a sensible indicator to evaluate the environmental quality of the soil. The objective of this study was to evaluate the organic carbon content of the soil in a toposequence in Serra do Teixeira, municipality of Teixeira, PB. Soil samples were collected in the upper third (UT), upper middle third (UMT), lower middle third (LMT) and lower third (LT) on three depths (0-5, 5-10 and 10-20 cm), with five replicates for each depth, resulting in a total of 60 samples. The organic carbon was evaluated using the methodology of Walkey-Black. Physical and chemical soil analysis were also carried out. The highest mean of carbon content was found in the first 5 cm (19.83 g dm-3), significantly differing from the other depths. It was also observed that the mean content of soil organic carbon on LMT was significantly higher than the other thirds, with 19.39 g dm-3. It is concluded that the highest contents of organic carbon are found on the most superficial layer of the soil. The organic carbon content variations found along the toposequence indicates influence of the relief and the anthropic action.